Experimental cooling mode variation of an air-cooled PEM fuel cell using second-order thermal analysis / Wan Ahmad Najmi Wan Mohamed and Rahim Atan - Wan Mohamed, Wan Ahmad Najmi; Atan, Rahim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
Thermal analysis of air-cooled Polymer Electrolyte Membrane (PEM) fuel cells for closed cathode designs are largely limited within first-order thermal analysis. Normally, closed cathode fuel cells apply the water cooling technique due to large cooling loads. Technical feasibility study in applying air cooling as an alternative for closed cathode stack designs is reported here using a down-scaled 3-cell stack assembly. A 242 cm2 active area, 3-cell closed cathode PEM fuel cell stack, was developed with 40 integrated straight path air cooling channels in order to investigate the internal thermal effects. The objective is to identify the bulk thermal effects of the stack under cooling for further design considerations using the second-order thermal analysis approach. Tests were conducted with airflows in the range between 200 and 400 Reynolds number and load variations from 10A to 30A. Different fan settings are applied to analyze the response of the design to negative and positive pressure airflows. The temperature profiles are translated into stack cooling profiles with discussions on its polarization, cooling response behaviour and cooling effectiveness. Generally, the cooling effectiveness across all cooling modes was higher than 80% and the negative pressure fan setting provides a more consistent cooling profile but with a slower cooling response.